Ontogenesis ; Public housing - Soh, Benjamin Jun Jie (Nanyang Technological University, 2020)
Ontogenesis; Public Housing is an antithesis that adopts an unequivocal opposite approach towards the present day design and construction process of the public housing in Singapore from built to finish. This project tackles a very pertinent problem by attempting to implement a next-gen technology that could perhaps materialize in the near future. Much like the principle of the aforementioned Biology process, the author believes that the state of our public housing today has yet to reach the level of complexity it can truly be.